Composites with Short Fibers Reinforced Epoxy Resin Matrix. (2016) - Matei, Simona; Stoicanescu, Maria; Crisan, Aurel
Abstract: The paper includes a research on the obtaining characteristics and physical-mechanical properties of the composites with short fibers reinforced epoxy resin matrix. We used four types of resins: T 19-38 / 500, T 19-38 / 700, L 50-54, A 19-00 and two types of reinforcing materials: Kevlar pulp and glass fiber. From the composites prepared in the injection phase (homogeneous mixture of matrix and fibers) were performed the standard samples to analyze the mechanical properties by pressing in a metallic mold. They were then subjected to a study to analyze the actual physical properties (density, component proportions) and mechanical properties (specific resistance, elastic modulus, elongation, etc.).